Child Care Subsidy Policy: Evaluation and Ways to Improve - Youngwook Lee (Korea Development Institute (KDI), 2015)
Child care policy in Korea revolves around financial support for all households with young children. However, the effectiveness of the approach varies among households. For example, high-income, highly educated families are less likely to use the subsidies to place their children in child care centers. In order to enhance the effectiveness of the child care policy and raise the employment of highly educated women, more attention should be placed on improving the quality of child care services rather than on universal financial support. - Child care support needs to be evaluated and explored to improve measures, taking into account the effectiveness and fiscal efficiency of the relevant child care policy. - The universal child care subsidy to households with children up to aged 2 contributed to an increase in the use of child care centers and decrease in the direct parental care of children, but little change was observed in women's labor supply. - For working mothers, the child care subsidy serves to replace informal care by caregivers (other than parents) with center-based care. - For less-educated, low income households, the use of child care centers has become a substitute for parental care, in contrast to highly educated, high-income households.
Keywords: 330